A longitudinal analysis of the executive functions in high-level soccer players - Beavan, A.; Chin, V.; Ryan, L. M.; Spielmann, J.; Mayer, J.; Skorski, S.; Meyer, T.; Fransen, J. (Journal of Sport & Exercise Psychology, 2020)
Introduction: Assessments of executive functions (EFs) with varying levels of perceptual information or action fidelity are common talent-diagnostic tools in soccer, yet their validity still has to be established. Therefore, a longitudinal development of EFs in high-level players to understand their relationship with increased exposure to training is required. Methods: A total of 304 high-performing male youth soccer players (10-21 years old) in Germany were assessed across three seasons on various sport-specific and non-sport-specific cognitive functioning assessments. Results: The posterior means (90% highest posterior density) of random slopes indicated that both abilities predominantly developed between 10 and 15 years of age. A plateau was apparent for domain-specific abilities during adolescence, whereas domain-generic abilities improved into young adulthood. Conclusion: The developmental trajectories of soccer players` EFs follow the general populations` despite long-term exposure to soccer-specific training and game play. This brings into question the relationship between high-level experience and EFs and renders including EFs in talent identification questionable. https://www.researchgate.net/publication/343208661_A_Longitudinal_Analysis_of_the_Executive_Functions_in_High-Level_Soccer_Players